Mergers, acquisitions, and other restructuring activities : an integrated approach to process, tools, cases and solutions - DePamphilis, Donald M. (London, United Kingdom ; San Diego, CA, United States : Academic Press, an imprint of Elsevier, 2022)
"Mergers, Acquisitions, and Other Restructuring Activities: An Integrated Approach to Process, Tools, Cases, and Solutions, Tenth Edition, is the most comprehensive and cutting-edge text available on the subject. Supported by recent peer-reviewed academic research, this book provides many recent, notable deals, precedent-setting judicial decisions, government policies and regulations, and trends affecting M&As, as well as takeover strategies and tactics. Today's policies, politics and economics are reflected in the book's 40 case studies, 90% of which involve deals either announced or completed during the last several years. These cases represent friendly, hostile, highly leveraged, and cross-border transactions in ten different industries, involving public and private firms and those experiencing financial distress. Sections discuss an overview of M&As, key regulations, common strategies and tactics, how managers may choose a business strategy from available options, valuation methods and basic financial modeling techniques, the negotiating process, how deal structuring and financing are inextricably linked, how consensus is reached during the bargaining process, the role of financial models in closing the deal and strategic growth options as alternatives to domestic M&As."
First edition: 2001
Includes bibliographical references (pages 523-540) and index.
Keywords: Organizational change -- United States -- Management; Consolidation and merger of corporations -- United States -- Management; Corporate reorganizations -- United States -- Management; Organizational change -- Management; Corporate reorganizations -- Management; Consolidation and merger of corporations -- Management; Consolidation and merger of corporations; Corporate reorganizations; United States